Prevention Strategies for HIV in Youth: A Concept Analysis - Sianturi, Sondang Ratnauli (Department of Nursing, Faculty of Medicine, Diponegoro University, 2015)
Purpose: To provide nurse educators how to address the problem of HIV/AIDS in the youth through the concept of prevention strategiesMethods: Review articles published during 2005 until 2014 that focused on HIV/AIDS prevention strategies. The databases used in this study were EBSCO, Medline, CINAHL, PubMed.Result: HIV knowledge is an important factor influencing HIV risk perceptions and risk behaviors especially among youth.The concept of prevention strategies designed and tested to address risk behavior on young people at every step along their developmental path. Strategies are very important ways for preventing HIV/AIDS, especially in youth. Conclusion: The attributes that characterize the concept of strategies are: plan, process, studying different ways, focusing on the greatest need, and analyzing and learning. Although strategies are used in prevention, they are not maximized in Indonesia. The best strategies for the different age groups have not yet been determined. With use of the best strategies, nurse educator can teach nursing students how best to reach youth and other people in the community to prevent HIV.